Pengaruh Sumber Daya Manusia Dan Internal Control Sebagai Variabel Moderating Terhadap Good Governance - Wulan Alawiyah; Purbasari, Heppy (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the effect of Human Resources (HR) and Internal Control (IC) as moderating variables on Good Governance practices. This research uses a quantitative approach with multiple linear regression analysis. The population of this study consists of 16 Unit Pengelola Kegiatan (UPK) in Sragen Regency, Central Java, with samples taken from the Chairman, Secretary, Finance Division, and Supervisory Board. The results show that HR significantly affects Good Governance (coefficient 0.263, significance 0.001), while Internal Control does not have a significant effect (coefficient -0.230, significance 0.631) and does not moderate the relationship between HR and Good Governance (interaction coefficient 0.011, significance 0.417). The limitations of this study include a limited scope and a cross-sectional research design. Future research is recommended to expand the scope and include variables such as organizational culture or information systems. It is also recommended that UPK strengthen its internal control systems to improve the structure of work processes.